Impact of chronic kidney disease on mortality: A nationwide cohort study - Kyeong Min Kim; Hyung Jung Oh; Hyung Yun Choi; Hajeong Lee; Dong-Ryeol Ryu (The Korean Society of Nephrology, 2019)
Background : Mortality is higher in patients with chronic kidney disease (CKD) than in the general population, but little information is available on CKD-related mortality that is representative of the Korean population. Our objective was to investigate mortality risk in Korean patients with CKD. Methods : We identified patients with incident CKD who had not undergone dialysis or kidney transplantation between January 1, 2003 and December 31, 2007 in Korea using the database of the Korean National Health Insurance Service-National Sample Cohort, and stratified the population into the following three groups: group 1 (n = 1,473), controls; group 2 (n = 2,212), patients with diabetes or hypertension, but without CKD; and group 3 (n = 2,212), patients with CKD. We then monitored them for all-cause mortality until December 2013. Results : A total of 1,473 patients were included in this analysis. During the follow-up period, 941 patients in group 3 died (134 deaths/1,000 person-years) compared with 550 deaths in the group 2 (34 deaths/1,000 person-years) and 459 deaths in group 1 (30 deaths/1,000 person-years). The rate ratio for mortality rate was 4.5, and the hazard ratio for mortality was 4.88 (95% confidence interval [CI], 4.36-5.47, P < 0.001) in patients in group 3 compared with age- and sex-matched controls (group 1). The rate ratio for mortality rate was 4.0, and the hazard ratio for mortality was 4.36 (95% CI, 3.92-4.85, P < 0.001) in patients in group 3 compared with patients in group 2. Conclusion : In this nationally representative sample cohort, excess mortality was observed in Korean patients with incident CKD.